Association between Children's Physical Activity and Parental Practices Enhancing Children's Physical Activity: The Moderating Effects of Children's BMI z-Score - Liszewska, Natalia; Scholz, Urte; Radtke, Theda; Horodyska, Karolina; Liszewski, Michal; Luszczynska, Aleksandra (Frontiers in Psychology, 2018)
Objective: Parental practices that aim at increasing children's physical activity were found to be related to children's physical activity. So far, however, the association between these two sets of variables was studied without considering the moderating role of children's BMI z-score, which may determine the effectiveness of parental practices. The present study aims at filling this void. Design: Longitudinal data were collected among 879 dyads of children (6–11 years old) and their parents. Seven parental physical activity practices were assessed at baseline. Physical activity, body mass, and height (measured among children) were assessed twice (at baseline and 7-month follow-up). Body mass and height were measured objectively. Seven moderation analyses were conducted. Results: Six parental practices emerged to predict physical activity of children: collaborative social control, overall support, stimulation to be active, general encouragement for physical activity, positive social control, and modeling. Children's BMI z-score moderated three associations. The relationships between parental positive social control, overall parental support, and general parental encouragement for physical activity (at baseline), and children's physical activity (at follow-up) were significant only among children with low and medium BMI z-score. In turn, collaborative social control and modeling predicted children's physical activity at the follow-up regardless child's BMI z-score. Conclusions: Parental positive social control or overall parental support may be ineffective in children with higher body mass who are in need to increase their physical activity.